Berry–Esseen type bound of conditional mode estimation under truncation and strong mixing assumptions. Issue 17 (1st September 2016) - Liang, Han-Ying; Li, Deli; Miao, Tianxuan
ABSTRACT: In order to investigate the convergence rate of the asymptotic normality for the estimator of the conditional mode function for the left-truncation model, we derive a Berry–Esseen type bound of the estimator when the lifetime observations with multivariate covariates form a stationary α-mixing sequence. The finite sample performance of the estimator of the conditional mode function is explored through simulations.